PENGARUH KOMPETENSI, INDEPEDENSI, DAN KOMITMEN ORGANISASI TERHADAP KINERJA AUDITOR PADA BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN (BPKP) PERWAKILAN SUMATERA UTARA - Riana Rantika Dwi Putri Br S.Kemb; Rizki Septiandre Isny; Dessy prasanti; Tetty Tiurma Uli Sipahutar (Jurnal Akrab Juara, 2019)
This study aims to examine whether competency, independence and organizational commitment influence the performance of government auditors in the Financial and Development Supervisory Agency (BPKP) of North Sumatra Representatives. The sample in research ii were 90 respondents. This study found that partially, the results of the study showed that the variable competence (X1), independence (X2) and organizational commitment (X3) had a positive and significant effect on the performance of government auditors. The F test results also show that simultaneously all the independent variables have a significant effect on the performance of the government auditor BPKP, this can be seen from a significant value of 6.944 where the value (6.944> 2.76) with a significant value of 0,000 is smaller than Î± = 0.05. The results showed that accepted and rejected means competency, independence and organizational commitment simultaneously had a significant effect on Auditor Performance at the Representative Office of North Sumatra's BPKP.